Birth defects that co‐occur with non‐syndromic gastroschisis and omphalocele. Issue 11 (4th September 2020) - Oluwafemi, Omobola O.; Benjamin, Renata H.; Navarro Sanchez, Maria Luisa; Scheuerle, Angela E.; Schaaf, Christian P.; Mitchell, Laura E.; Langlois, Peter H.; Canfield, Mark A.; Swartz, Michael D.; Scott, Daryl A.; Northrup, Hope; Ray, Joseph W.; et al.
Abstract: Gastroschisis and omphalocele are the two most common abdominal wall birth defects, and epidemiologic characteristics and frequency of occurrence as part of a syndromic condition suggest distinct etiologies between the two defects. We assessed complex patterns of defect co‐occurrence with these defects separately using the Texas Birth Defects Registry. We used co‐occurring defect analysis (CODA) to compute adjusted observed‐to‐expected (O/E) ratios for all observed birth defect patterns. There were 2, 998 non‐syndromic (i.e., no documented syndrome diagnosis identified) cases with gastroschisis and 789 (26%) of these had additional co‐occurring defects. There were 720 non‐syndromic cases with omphalocele, and 404 (56%) had additional co‐occurring defects. Among the top 30 adjusted O/E ratios for gastroschisis, most of the co‐occurring defects were related to the gastrointestinal system, though cardiovascular and kidney anomalies were also present. Several of the top 30 combinations co‐occurring with omphalocele appeared suggestive of OEIS (omphalocele, exstrophy of cloaca, imperforate anus, spinal defects) complex. After the exclusion of additional cases with features suggestive of OEIS in a post‐hoc sensitivity analysis, the top combinations involving defects associated with OEIS (e.g., spina bifida) were no longer present. The remaining top combinations involving omphalocele included cardiovascular, gastrointestinal, and urogenital defects. In summary, we identified complex patterns of defects that co‐occurred more frequently than expected with gastroschisis and omphalocele using a novel software platform. Better understanding differences in the patterns between gastroschisis and omphalocele could lead to additional etiologic insights.